Model kinerja karyawan melalui efektivitas kerja pada PT. Batanghari Barisan - Fasridon; Angraini, Yuli (Riset Sinergi Indonesia, 2023)
his study aims to determine the effect of work from home (wfh) and work discipline on employee performance with work effectiveness as an intervening variable at PT. Batanghari Barisan Padang, This research is a quantitative study. The data collection method is through a questionnaire, with a sample of 68 respondents from PT. Batanghari Padang Row. The analytical methods used are path analysis, partial least squares (PLS) analysis, outer model, inner model and hypothesis testing. Data processing in this study used the SmartPLS 3.0 software program. The results of the study can be concluded that work from home (wfh) has a positive and not significant effect on effectiveness, work discipline has a positive and significant effect on effectiveness, work from home (wfh) has a positive and not significant effect on employee performance, work discipline has a positive and significant effect on employee performance, effectiveness has a positive and insignificant effect on employee performance, and effectiveness is not able to mediate work from home (wfh), work discipline on employee performance at PT. Batanghari Padang Row